The Jersey Shore : the past, present & future of a national treasure - Mazzagetti, Dominick A. (Rutgers University Press, 2018)
The Jersey Shore tells the story of this famous region, from the 1600s to the present, and from Sandy Hook to Cape May, with particular attention to its history, culture, and varied landscapes. This book is an enthusiastic and comprehensive portrait by a native son, whose passion is shared by millions of beachgoers.